2022
DOI: 10.1039/d2na00463a
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-chromatic probe based lateral flow assay for point-of-care detection of Japanese encephalitis virus NS1 protein biomarker in clinical samples using a smartphone-based approach

Abstract: Lateral flow assays (LFAs) are one of the most economical, point-of-care (PoC) diagnostic assays that exploit the colorimetric properties of gold nanoparticles (AuNPs) but no rapid antigen-based LFA exists for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 55 publications
(72 reference statements)
0
10
0
Order By: Relevance
“… 30 , 31 The sample pad and the conjugate pads are pretreated before assembly for the equilibration of the membrane, antifouling of the membrane pores, and easy flow of the analyte across the membrane. 29 Moreover, variations in conjugate deposition, drying, and membrane release, all contribute significantly to the coefficient of variation in test performance. The sample is loaded on the pretreated sample pad, enabling it for interaction with the AuNPs‐Ab probe deposited on the conjugate pad.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 , 31 The sample pad and the conjugate pads are pretreated before assembly for the equilibration of the membrane, antifouling of the membrane pores, and easy flow of the analyte across the membrane. 29 Moreover, variations in conjugate deposition, drying, and membrane release, all contribute significantly to the coefficient of variation in test performance. The sample is loaded on the pretreated sample pad, enabling it for interaction with the AuNPs‐Ab probe deposited on the conjugate pad.…”
Section: Resultsmentioning
confidence: 99%
“…Several new labels such as colloidal gold nanoparticles (AuNPs), 24 , 25 gold nanorods, 26 silver enhancement technology, and carbon and magnetic nanomaterials 27 accompanied with enzymes (horseradish peroxidase) supports the improvement of quantification system, but their synthesis process is difficult and expensive. Therefore, AuNPs are prominently used in LFIA due to its unique optical property, biocompatibility with different biomolecules, stability, 28 , 29 cost‐effectiveness, and easy synthesis. Currently, several LFIAs have been developed and commercialized in the market, of which the majority of them are serological‐based assays and rely on previous SARS‐CoV‐2 exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In general, LFAs utilize antibodies as recognition elements and AuNPs as reporter probes, and the detection result is directly visualized on the test strip without requiring external energy sources [ 24 ]. For instance, Roberts et al reported a portable LFA for on-site detection of the Japanese Encephalitis virus in serum ( Figure 1 a) [ 25 ]. Using AuNPs as immunoprobes, the test line turned red in the presence of the antigen, with a limit of detection (LOD) of 10 pg/mL within 10 min.…”
Section: Virus Detection On Microfluidic Platformmentioning
confidence: 99%
“… ( a ) Schematic representation of the colorimetric sandwich-based LFA for rapid detection of the Japanese Encephalitis virus using gold nanoparticles. Reprinted with permission from [ 25 ]. Copyright (2022) RSC publications.…”
Section: Figurementioning
confidence: 99%
“…The LFA was able to successfully detect JEV Ab in 500 clinical pig serum real samples with 100% relative diagnostic specificity as well as sensitivity in monsoon and post-monsoon (Dhanze et al 2019 ). Another recently developed LFA using AuNPs conjugated with JEV NS1 Ab as immunochromatic probes was fabricated for successful point of care detection of JEV NS1 Ag in clinical pig serum samples with a visual LOD of 10 pg/ml (Roberts et al 2022d ).…”
Section: Biosensors For Jev Diagnosticsmentioning
confidence: 99%